Microwave-assisted synthesis of novel Ti/BTB-MOFs as porous anticancer and antibacterial agents - Altharawi, Ali; Alqahtani, Safar M.; Aldakhil, Taibah; Ahmad, Irfan (Frontiers in Chemistry, 2024)
Nano compounds, especially MOFs, have significant properties in various areas. One of the most important properties of these compounds, which depends on their specific surface area and porosity, are biological properties, such as anticancer and antibacterial properties. In this study, by using Titanium nitrate and 1,3,5-Tris(4-carboxyphenyl)benzene (BTB) under microwave radiation, a new Titanium/BTB metal-organic framework was synthesized (Ti/BTB-MOF). Using XRD, XPS, FT-IR, EDAX and EDAX mapping, SEM, TGA, and BET, the structure of the synthesized Ti/BTB-MOF were characterized and confirmed. The in vitro anticancer properties of Ti/BTB-MOF using the MTT method against MG-63/bone cancer cells and A-431/skin cancer cells were evaluated. By using the clinical and laboratory standards institute (CLSI) guidelines, the in vitro antibacterial activity were tested. In the anticancer activity, IC50 (Half-maximal inhibitory concentration) 152 μg/ml and 201 μg/ml for MG-63/bone cancer cells and A-431/skin cancer cells were observed. In the antibacterial activity, MIC (minimum inhibitory concentration) against studied pathogenic strains, between 2 -64 μg/ml were observed. The antimicrobial activity of Ti/BTB-MOF was higher that of penicillin and gentamicin. Therefore, the synthesized Ti/BTB-MOF can be introduced as a suitable bioactive candidate.